A Performance Analysis of Native JSON Parsers in Java, Python, MS.NET Core, JavaScript, and PHP - Dhalla, Hardeep Kaur (International Conference on Network and Service Management (Print), 2020)
JavaScript Object Notation (JSON) has gained prominence over Extensible Markup Language (XML) due to its lightweight and flexible nature. This has also made it a first-class citizen when it comes to choose a data interchange format. All major programming platforms provide native libraries to parse JSON formatted data, but the performance of JSON parsers varies with their implementation. For further processing and analysis of semi-structured JSON data, it is first parsed which is expensive. In this research paper, performance analysis of JSON parsers in the native environment of 5 different programming languages has been done in terms of parsing speed and resource consumption. The experiment data is created using an algorithm written in Java that generates 10 different JSON files with an increasing number of key-value pairs at each level of JSON nesting. The native performance monitor on Windows 10 operating system is used to monitor and measure memory and CPU usage of the running processes. The output of data collector set is saved in the comma separated format for further analysis. The experimental results are discussed and shared at the end.